KEMANDIRIAN BELAJAR MAHASISWA TADRIS MATEMATIKA FTIK IAIN PALU SELAMA MASA PEMBELAJARAN DARING - Rafiq Badjeber (Koordinat Jurnal MIPA, 2020)
This Research aims to describe student’s self-regulated learning at Tadris Matematika FTIK IAIN Palu during the online learning period. This research is descriptive quantitative with survey method. Data collection techniques using an online questionnaire given to 20 students of the 2nd semester in Tadris Matematika FTIK IAIN Palu. The results showed that more than 70% of Students in Tadris Matematika were already good in aspect setting learning goals/targets, viewing difficulties as challenges and evaluating learning processed and outcomes. However, more than 60% are still not good in terms of initiative and intrinsic learning motivation, diagnosed their own learning needed, monitoring, managing and controlling learning, utilizing and searching for relevant resources, choose and implemented strategy of learning and abilities.